เซมิกรุปเรกูลาร์สตาร์และเซมิกรุปสตาร์เรกูลาร์ - ศรีบุตร แววเจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 1980)
In this thesis, various properties of regular-* semigroups and *-regular semigroups are compared. The main purpose of this thesis is to show that for any set X, the partial transformation semigroup, the full transformation semigroup, the semigroup of almost identical partial transformations or the semigroup of almost identical full transformations on the set X is regular-* or *-regular if and only if the cardinality of X is less than or equal to one. Moreover, we introduce well – know congruences which preserve * on some *-semigroups. The following are shown : The minimum semilattice congruence on any *-semigroup, the maximum idempotent- separating congruence on any *-swmigroup, the maxium idempotent-separating congruence on an orthodox semigroup which is a *-semigroup, the minimum group congruence on an inverse semigroup which is a *-semigroup, the minimum inverse congruence on an orthodox semigroup which is a *-semigroup and the maximum congruence contained in the Green’s relation of a regular semigroup which is a *-semigroup are all *-congruences.